Making the Void Fruitful Yeats As Spiritual Seeker and Petrarchan Lover - Keane, Patrick J.
Shedding fresh light on the life and work of William Butler Yeats--widely acclaimed as the major English-language poet of the twentieth century--this new study by leading scholar Patrick J. Keane questions established understandings of the Irish poet's long fascination with the occult: a fixation that repelled literary contemporaries T.S. Eliot and W.H. Auden, but which enhanced Yeats's vision of life and death